Development of gas separation system by membranes - Preliminary results of membranes characterization - Saidi, Hamdani; Abdul Aziz, Ramlan; Salleh, I. K.; Hassan, H. (1991)
The huge natural gas found in Malaysia has necessitated research and development in new technologies of gas processing. Membranes technology is not only the latest and most advanced system but also requires less cost of maintenance. This paper presents the preliminary results of membrane characterization for CO2 separation from natural gas. It is a part of the overall project to develop CO2 gas separation system using membrane from natural gas funded by IRPA.